2015
DOI: 10.1007/s11229-015-0888-9
|View full text |Cite
|
Sign up to set email alerts
|

Doing without believing: Intellectualism, knowledge-how, and belief-attribution

Abstract: We consider a range of cases-both hypothetical and actual-in which agents apparently know how to ϕ but fail to believe that the way in which they in fact ϕ is a way for them to ϕ . These "no-belief" cases present a prima facie problem for Intellectualism about knowledge-how. The problem is this: if knowledge-that entails belief, and if knowing how to ϕ just is knowing that some w is a way for one to ϕ , then an agent cannot both know how to ϕ and fail to believe that w, the way that she ϕ s, is a way for her t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…The idea of a mismatch between an agent's avowed beliefs and know-how is not unique to the case of joint action. Brownstein and Michaelson (2016) consider various cases in which an agent appears to know how to perform some individual action while believing, of the way he implements, that it cannot lead to success. However, as Brownstein andMichaelson (2016, p. 2830) acknowledge, the intellectualist can seek to account for these examples by positing beliefs held under a practical mode of presentation that contradict the agent's avowed beliefs (Stanley and Williamson 2001;Stanley 2011, Ch.…”
Section: Practical Modes Of Presentationmentioning
confidence: 99%
“…The idea of a mismatch between an agent's avowed beliefs and know-how is not unique to the case of joint action. Brownstein and Michaelson (2016) consider various cases in which an agent appears to know how to perform some individual action while believing, of the way he implements, that it cannot lead to success. However, as Brownstein andMichaelson (2016, p. 2830) acknowledge, the intellectualist can seek to account for these examples by positing beliefs held under a practical mode of presentation that contradict the agent's avowed beliefs (Stanley and Williamson 2001;Stanley 2011, Ch.…”
Section: Practical Modes Of Presentationmentioning
confidence: 99%
“…For one thing, it is an open question whether truth, belief justification pertain to knowledge-how. It is easy to find views on which knowledge-how is connected to truth (Stanley and Williamson 2001), belief (Brownstein and Michaelson, 2015), and justification (Hawley 2003), (Brogaard 2011). Putting this issue to one side, even if it turned out that these conditions do not pertain to knowledge-how, this would not JNS: It is permissible to show someone how to V in way w, only if one has a justified belief that w is a way to V. 14 As in the case of assertion, these norms need not be mutually exclusive.…”
Section: What Are the Alternatives To Knowledge?mentioning
confidence: 99%
“…Finally, some have observed that know how may differ from propositional knowledge in that, whereas the latter plausibly entails belief, know how does not (Wallis, ; Brownstein & Michaelson, ). For example, studies show that when catching a ball, ball players make anticipatory saccades to shift their gaze ahead of the ball one or more times during the course of its fight towards them.…”
Section: Arguments Against Intellectualism About Know Howmentioning
confidence: 99%
“…In response, Pavese has developed a Fregean notion of practical modes of presentation-as practical senses-and has argued that examples of practical senses can be found in operational semantic values for programming languages (Pavese, 2015b). 11 Finally, some have observed that know how may differ from propositional knowledge in that, whereas the latter plausibly entails belief, know how does not (Wallis, 2008;Brownstein & Michaelson, 2015). For example, studies show that when catching a ball, ball players make anticipatory saccades to shift their gaze ahead of the ball one or more times during the course of its fight towards them.…”
Section: However Recently This Diagnosis Of Cath's Examples Has Beenmentioning
confidence: 99%
See 1 more Smart Citation